Asal-usul Dewey Decimal Classification: melacak pemikiran Melvil Dewey dalam organisasi pengetahuan - Anis Masruri; Khusnul Khotimah (Al Maktabah, 2017)
The library material needs to be classified according to the content or subject to be easily recoveredwhen searched by library users. To classify the library materials required a classificationguideline. The most popular and widely used Classification Guidelines are Dewey DecimalClassification (DDC). This DDC was created by Melvil Dewey. In fact, Melvil Dewey is not theabsolute inventor of DDC, because he was influenced by previous scientists, such as S.F. Bacon,William Torrey Haris, William Phipps Blake, Schwartz and Hegel’s philosophy. Nevertheless,Melvil Dewey is considered to have a very important role so known as the Father of ModernLibrarianship. This paper reveals the origin of Dewey Decimal Classification (DDC) and theprocess of making it.